Tinjauan Yuridis Terhadap Kontribusi Hukum Bisnis Di Indonesia - Oddang, Yoram (Journal of Law and Administrative Science, 2023)
bstract. This study discusses the juridical review of the contribution of business law in Indonesia. In human life, basically doing social relations and social interactions occur that can lead to or create networks of social relations with their environment or called a Web of Social Relationship. In the dynamics of this life, every human being / person needs a certainty to be able to achieve the goal in order to run safely and orderly. Therefore, the function of law in society is very important. Similarly, when they do business efforts. Because the business will calculate profit and loss, so that there is no chaos, the Government makes laws or regulations regarding business in Indonesia, so that these activities can run smoothly, orderly and safely and comfortably. So regulations were made such as Article 33 of the 1945 Constitution, Law no. 25/1992 on Cooperatives, TAP MPR No. XVI/MPR/1998 concerning Economic Politics in the context of Economic Democracy, through a Special Session and several other laws or regulations such as the Republic of Indonesia Law no. 8/1995 concerning Capital Market, RI Law no. 40/2007 concerning Limited Liability Companies (PT), RI Law no. 24/2002 concerning Government Securities, BAPEPAM-LK Regulations, Indonesia Stock Exchange Regulations (dh JSE and BES), Indonesian Central Securities Depository Regulations (KSEI) and Indonesian Clearing and Guarantee Corporation Regulations (KPEI), as well as other regulations all of which is a guide for business actors in Indonesia to be clear and firm, so that business can be carried out consistently in the implementation of its operations in society and the State.